2017
DOI: 10.1002/chem.201605895
|View full text |Cite
|
Sign up to set email alerts
|

A Cryptand Metal–Organic Framework as a Platform for the Selective Uptake and Detection of Group I Metal Cations

Abstract: The metal-organic framework (MOF) complex (H O) [Zn (ur)(Hfdc) (fdc) ] (1, ur=urotropine, H fdc=furan-2,5-dicarboxylic acid) incorporates cryptand-like cavities, which can be used to separate and detect Rb and Cs optically. This is the first example of the effective employment of a MOF material for optical detection of these cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Although this field is well‐recognized and sustainability idea is known, the primary requirement nowadays is to develop good procedures for organic synthesis with bio‐derived blocks and there is a keen interest in exploring chemical reactivity of biomass‐derived platform compounds . With developing a series of bio‐derived synthetic building blocks with different functional groups, the scope of application of biomass‐derived products was expanded, such as synthetic drugs, metal organic frameworks, and functional materials . Due to the carbonhydrates structure of lignocellulose, the bio‐derived products are mainly oxygen containing compounds .…”
Section: Figurementioning
confidence: 99%
“…Although this field is well‐recognized and sustainability idea is known, the primary requirement nowadays is to develop good procedures for organic synthesis with bio‐derived blocks and there is a keen interest in exploring chemical reactivity of biomass‐derived platform compounds . With developing a series of bio‐derived synthetic building blocks with different functional groups, the scope of application of biomass‐derived products was expanded, such as synthetic drugs, metal organic frameworks, and functional materials . Due to the carbonhydrates structure of lignocellulose, the bio‐derived products are mainly oxygen containing compounds .…”
Section: Figurementioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are highly crystalline porous solids that provide diverse chemical and physical pore environments and qualify as good platforms to study host-guest interactions in the solid state. Similar to zeolites, MOFs containing exchangeable alkali metal ions have been studied for various purposes such as luminescent sensors, [16][17] proton conductors, 18 ionselective membranes, 19 solid electrolytes 20 and enhanced gas uptake, [21][22][23][24] to name a few. Consequently, detailed structural information on the coordination of alkali metal ions in porous solids would be highly desirable to better understand and improve material properties toward above-mentioned applications.…”
Section: Introductionmentioning
confidence: 99%
“…Other than a bent shape, the striking feature of ditopic dicarboxylate linkers based on heterocyclic core (Scheme 1) is the polarity of the core and the polarizability of a heteroatom, enabling additional induced dipole interactions with a substrate. Recently, a number of research groups have shown that the incorporation of 2,5-furanedicarboxylate (fdc 2− ) or 2,5-thiophenedicarboxylate (tdc 2− ) into porous MOF structures imbue such materials with quite unique features such as selective ion adsorption, luminescence sensing [20][21][22], dielectric bistability [23], and gas/vapor uptake [24,25].…”
Section: Introductionmentioning
confidence: 99%